Effect size of Dna-j heat shock protein family B member 9 (DNAJB9) biomarker in kidney biopsy specimens on kidney outcomes in fibrillary glomerulonephritis - Fateme Shamekhi Amiri (Počki, 2022)
Background. Fibrillary glomerulonephritis is a rare glomerular disease that presents with hypertension, hematuria, nephrotic syndrome and renal insufficiency. The purpose of this research was to assess effect of DNAjB9 staining marker in kidney biopsy specimens on kidney outcomes. Materials and methods. In this analytic (experimental) clinical study with randomized clinical trial design in meta-analysis article, 72 patients with biopsy-proven fibrillary glomerulonephritis were investigated. Clinical features, laboratory data at initial presentation, management and outcomes were collected. The paper has written based on searching PubMed Central and Google Scholar to identify potentially relevant articles. Median, percentage, mean ± standard deviation (SD), two-tailed t and Chi-square, two proportion difference meta-analysis and Kaplan-Meier analysis were used for statistical evaluation. Moreover, relative risk, odds ratio, Spearman’s correlation for statistical analyses were used. Results. The median and interquartile range of age of patients with fibrillary nephropathy at the time of diagnosis were 55 and 18 years, respectively. There was no statistically significant difference between two sex groups of males and females in current research (p-value: 0.35). There was significant statistical correlation between elevated serum creatinine level and time of last serum creatinine measurement with p-value of 0.01 and confidence interval (CI) of 0.7820 to –0.1258 during follow-up. Relative risk of kidney failure progression to kidney replacement therapy (↑ ≥ 2-fold in serum creatinine or dialysis or kidney transplant) in DNAjB9-positive (group I) and DNAjB9-negative patients (group II) was assessed 2.67 with 95% CI of 1.128 to 6.3044 and p-value of 0.025. Odds ratio of kidney failure progression to kidney replacement therapy (↑ ≥ 2-fold in serum creatinine or dialysis or kidney transplant) was assessed 4.33 with 95% CI of 0.9464 to 19.8417 and p-value of 0.058. There was statistically significant difference when comparing group I and group II for mortality probability (Kaplan-Meier analysis) during follow-up (P < 0.0001). Conclusions. The present study revealed high mortality in DNAjB9-negative (8/64, 12.5%) versus DNAjB9-positive patients (0/8) with statistically significant level. Relative risk and odds ratio of kidney failure progression to kidney replacement therapy were assessed 2.67 and 4.33, respectively.